1968
DOI: 10.1111/j.1432-1033.1968.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Gramicidin S Synthesizing Activity in Bacillus brevis Extracts

Abstract: A 20 fold purification of the gramicidin S synthesizing activity in a 11,OOOxg supernatant from Bacillus brevis has been achieved. The purification procedure involves precipitation of undesired material with streptomycin sulphate, followed by precipitation of gramicidin S synthesizing activity a t 40°/, (NH,),SO, saturation and fractionation on DEAE-Sephadex. All gramicidin S synthesizing activity appeared in one peak. It incorporated labelled phenylalanine, proline, valine, ornithine and leucine to the same e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Earlier studies on the biosynthesis of gramicidin S have indicated that RNA does not participate [ 1,3]. The present result is therefore in agreement with this earlier finding.…”
Section: Resultssupporting
confidence: 94%
“…Earlier studies on the biosynthesis of gramicidin S have indicated that RNA does not participate [ 1,3]. The present result is therefore in agreement with this earlier finding.…”
Section: Resultssupporting
confidence: 94%
“…The development of cell-free systems for the synthesis of GS1 and Ty made it possible to decipher the mechanism of biosynthesis of these cyclic decapeptides by nonribosomal systems (Saito et al, 1970;Kurahashi et al, 1969;Bredesen et al, 1968;Lipmann et al, 1971). These studies showed that the amino acids are activated by ATP on complementary enzymes of a molecular weight roughly proportional to the number of amino acids activated.…”
mentioning
confidence: 99%
“…This observation suggested auto-oxidation as an in vitro inactivation mechanism. Many reports of cellfree synthesis systems allude to the fact that reducing agents are required for short-term incubation (14)(15)(16)25) and long-term stabilization (2,7). Enhancement of stability by thiol reagents indicates that auto-oxidation (formation of enzyme disulfide) is compensated for by increased disulfide exchange with the thiol reagent (3,23).…”
Section: Atp-ppi Exchange Activity Was Investigatedmentioning
confidence: 99%
“…Gramicidin S (GS) synthetase is an enzyme complex responsible for the nonribosomal biosynthesis of GS in Bacillus brevis. The complex includes both a heavy (280,000 daltons) and a light (100,000 daltons) enzyme and catalyzes the formation of the cyclic decapeptide GS: 2 In the first step of GS biosynthesis, the individual amino acids are activated by ATP, which results in the formation of aminoacyl adenylates (7,12,21). The light enzyme catalyzes activation and racemization of L-to Dphenylalanine, and the heavy enzyme activates I Presnt address: George Washington University Law School, Washington, DC 20003. the other constituent amino acids (10).…”
mentioning
confidence: 99%